Probing the diabetes and colorectal cancer relationship using gene - environment interaction analyses - Dimou, Niki; Kim, Andre E; Flanagan, Orlagh; Murphy, Neil; Diez-Obrero, Virginia; Shcherbina, Anna; Aglago, Elom K; Bouras, Emmanouil; Campbell, Peter T; Casey, Graham; Gallinger, Steven; Gruber, Stephen B; et al. (British journal of cancer, 2023)
BACKGROUND: Diabetes is an established risk factor for colorectal cancer. However, the mechanisms underlying this relationship still require investigation and it is not known if the association is modified by genetic variants. To address these questions, we undertook a genome-wide gene-environment interaction analysis. METHODS: We used data from 3 genetic consortia (CCFR, CORECT, GECCO; 31,318 colorectal cancer cases/41,499 controls) and undertook genome-wide gene-environment interaction analyses with colorectal cancer risk, including interaction tests of genetics(G)xdiabetes (1-degree of freedom; d.f.) and joint testing of Gxdiabetes, G-colorectal cancer association (2-d.f. joint test) and G-diabetes correlation (3-d.f. joint test). RESULTS: Based on the joint tests, we found that the association of diabetes with colorectal cancer risk is modified by loci on chromosomes 8q24.11 (rs3802177, SLC30A8 - ORAA: 1.62, 95% CI: 1.34-1.96; ORAG: 1.41, 95% CI: 1.30-1.54; ORGG: 1.22, 95% CI: 1.13-1.31; p-value3-d.f.: 5.46 × 10-11) and 13q14.13 (rs9526201, LRCH1 - ORGG: 2.11, 95% CI: 1.56-2.83; ORGA: 1.52, 95% CI: 1.38-1.68; ORAA: 1.13, 95% CI: 1.06-1.21; p-value2-d.f.: 7.84 × 10-09). DISCUSSION: These results suggest that variation in genes related to insulin signaling (SLC30A8) and immune function (LRCH1) may modify the association of diabetes with colorectal cancer risk and provide novel insights into the biology underlying the diabetes and colorectal cancer relationship.
Keywords: Genetic Predisposition to Disease; rizikové faktory; Diabetes Mellitus; Colorectal Neoplasms; Gene-Environment Interaction; interakce genů a prostředí; celogenomová asociační studie; genetická predispozice k nemoci; jednonukleotidový polymorfismus; Humans; Risk Factors; kolorektální nádory; Genome-Wide Association Study; diabetes mellitus; Microfilament Proteins; lidé; Polymorphism, Single Nucleotide; mikrofilamentové proteiny